2007
DOI: 10.1080/13651500600885531
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the BASIS-24© (Behaviour and Symptom Identification Scale–Revised) Mental Health Outcome Measure

Abstract: Objective. Outcome measurement in mental health services is an area of considerable clinical interest and policy priority. This study sought to assess the Behaviour and Symptom Identification Scale-24 (BASIS-24©), a brief, patient self-reported measure of psychopathology and functioning, in a UK sample, including establishing population norms for comparative purposes. Methods. Participants were 588 adults recruited from psychiatric inpatient, outpatient and primary care settings; and 630 adults randomly sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 11 publications
1
71
0
Order By: Relevance
“…The SMS is used to assess the extent of difficulty in controlling substance behaviours over the past week. Internal consistency for the Substance Misuse Scale in a clinical population has been reported to be .85 (Cameron et al 2007). In the present study, both internal consistency of the SMS and test-retest reliability was found to be at acceptable levels (r=.77 in both cases).…”
Section: Methodsmentioning
confidence: 94%
“…The SMS is used to assess the extent of difficulty in controlling substance behaviours over the past week. Internal consistency for the Substance Misuse Scale in a clinical population has been reported to be .85 (Cameron et al 2007). In the present study, both internal consistency of the SMS and test-retest reliability was found to be at acceptable levels (r=.77 in both cases).…”
Section: Methodsmentioning
confidence: 94%
“…The Center for the Epidemiological Studies of Depression-10 (CES-D-10) (Andresen et al, 1994) is a brief instrument for measuring depressive symptoms. The BASIS-24 (Cameron et al, 2007;Eisen et al, 2004) is a 24-item measure consisting of six subscales that assess past week symptoms. For the current study, we utilized the Substance Abuse/Dependence, Interpersonal Problems, Psychosis, and Emotional Lability subscales, and the single item assessing suicidal ideation.…”
Section: Methodsmentioning
confidence: 99%
“…The Behavior and Symptom Identification Scale (BASIS-24; Cameron et al, 2007) is a validated 24-item measure assessing the frequency with which participants have experienced specific symptoms and impairments in functioning over the past week on a 5-point scale. It includes six subscales, depression/functioning, interpersonal problems, self-harm, emotional lability, substance abuse, and psychosis.…”
Section: Materials and Proceduresmentioning
confidence: 99%